Angiotensin converting enzyme as a genetic risk factor for coronary artery spasm. Implication in the pathogenesis of myocardial infarction. - Y Oike; A Hata; Y Ogata; Y Numata; K Shido; K Kondo (The Journal of Clinical Investigation, 1995)
It has been reported that individuals with the D allele of an insertion/deletion (I/D) polymorphism of the angiotensin converting enzyme (ACE) gene are at greater risk for myocardial infarction (MI), especially among subjects normally considered to be at low risk. However, little is known about the mechanism by which the ACE polymorphism affects the risk of MI. Coronary artery spasm (CAS) is considered to be one possible mechanism for developing MI. We therefore examined the ACE polymorphism relation to CAS to determine if this was the mechanism by which the DD genotype influences MI. We studied 150 angiographically assessed Japanese males, all more than 60 yr old. CASs were detected using intracoronary injection of ergonovine maleate. Subjects were divided into three groups: those with CAS (group 1), those without CAS, but with fixed organic stenosis (group 2); and those without CAS and no organic stenosis (group 3). DD subjects were significantly represented in group 1 when compared with groups 2 (P = 0.002) and 3 (P = 0.026). These results suggest that the DD genotype relates to the greater risk for MI in the patients with CAS.